Exploring Multi-Channel Shopping Behavior Towards It & C Products, Based on Business Students Opinions - Cristinel Vasiliu; Mihai Felea; Irina Albăstroiu; Irina Albăstroiu (Amfiteatru Economic)
Young people have rapidly adopted the practice of using a variety of channels through which to shop, especially for products that require thorough information on features and price. IT & C products fall into this category, and buyers using multiple channels benefit from the advantages of information from online stores and reduced risks associated with the acquisition from traditional stores. The aim of this article is to identify young people preference for buying IT & C products from companies that distribute them across multiple channels. In this regard, an exploratory research was conducted on a sample of 340 students. The main results showed the high frequency use of Internet as a means of searching the information needed for purchasing IT & C products, the low share of exclusively online purchase, the fact that they are being perceived by students as both a need and a desire, and the weak expression of views about products purchased in the virtual environment. Price and quality are the main criteria in choosing them. Originality of this article is determined by identifying students’ preference for firms practicing multi-channel distribution strategy for IT & C products. Basically, people that we investigated gather online information about these products, from companies’ sites, but they mainly buy them in traditional stores.